Comprehensive Mass Spectrometric Analysis of Snake Fruit: Salak (Salacca zalacca) - Petra Hlásná Čepková; Michal Jágr; Dagmar Janovská; Václav Dvořáček; Anna Kotrbová Kozak; Iva Viehmannová (Journal of Food Quality)
Snake fruit (Salacca zalacca (Gaert.) Voss) is a fruit species traditionally cultivated in Indonesia and other Southeast Asian countries. The edible parts of the fruits contain a certain amount of total phenolic, flavonoid, and monoterpenoid compounds, proving them to be their perfect sources. The main goal of this work was to detect, quantify, and identify various phenolic compounds present in snake fruit pulp. Ultrahigh performance liquid chromatography coupled to a Q-Orbitrap tandem mass spectrometer was able to detect 19 phenolic compounds in the salak pulp, including 5 flavanols, 6 phenolic acids, 2 flavonols, 1 flavone, and also 5 presumably new phenolic compounds. Among the detected compounds, 11 were reported and quantified for the first time in salak pulp. Chlorogenic acid was by far the most predominant phenolic compound. The next relatively abundant compounds in snake fruit were epicatechin, isoquercetin, neochlorogenic acid, ferulic acid, gallic acid and procyanidine B2 (levels at ca 5–10 μg/g in MeOH extract), syringic acid, and caffeic acid (levels at ca 1 μg/g in H2O extract). A significant total phenolic content (257.17 μL/mL) and antioxidant activities (10.56 μM TE/g of fruit pulp) were determined. In conclusion, S. zalacca fruit has potential to serve as a natural source of phenolic compounds with antioxidative activities which may be associated with their health benefits.